CAPABILITY OF MITOCHONDRIA DNA D-LOOP MARKERS FOR SHARK SPECIES IDENTIFICATION - Estu Nugroho (Research Center for Fisheries, 2001)
ldentification of dry-fin shark was conducted by mitochondria DNA (mtDNA) D-loop markers. Eighteen of thiity samples have been successfully amplified the mtDNA D-loop region.